Pengaruh Pengungkapan Enviromental, Social dan Governance (ESG) Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Perbankan Yang Terdaftar di BEI Tahun 2023) - Nasution, Maulana Ikbal Saputra; Yulia, Iis Anisa; Fitrianti, Dewi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to analyze the impact of Environmental, Social, and Governance (ESG) disclosures on firm value. The sample consists of banking companies listed on the Indonesia Stock Exchange (IDX) in 2023. The sampling method employed is purposive sampling, with hypothesis testing conducted using multiple linear regression. The results indicate that Environmental Disclosure has a significant impact on firm value, while Social Disclosure does not have a significant effect. Governance Disclosure also has a significant impact on firm value. Furthermore, simultaneous analysis reveals that ESG disclosures, as a collective, significantly affect firm value. These findings suggest that although Social Disclosure does not individually impact firm value, the overall integration of ESG aspects influences investors' perception of a company's value